UTILIZATION OF YOUTUBE-BASED DIGITAL MEDIA IN SCIENCE LEARNING IN ELEMENTARY SCHOOLS - Sepling Paling (International Journal of Teaching and Learning, 2024)
Digital media is a means of delivering information from the sender to the recipient. YouTube videos as a learning medium are very suitable for the learning characteristics of today's generation of students, so students prefer to watch learning videos via YouTube. Using YouTube media for learning, especially science learning, can help students develop critical thinking skills, solve problems, make decisions, and use social media to collaborate. YouTube can provide students and teachers with valuable experiences for freedom of expression, educational collaboration, and skill development. Innovating YouTube videos to teach science, they must be systematic, concrete and complex. The content of YouTube content contains four main elements in the nature of IPA. YouTube video innovations that suit the nature of science learning are carried out in the form of five types of videos, namely (1) concept explanation videos, (2) scientific facts videos, (3) model simulation videos, (4) demonstration videos and (5) experimental videos. Learning videos on YouTube can be used for interactive learning in the classroom, both for students and teachers themselves through online and offline presentations.